TRANSFORMASI PENGELOLAAN BUMDES: PELATIHAN FORECASTING BAGI GENERASI Z - Ghea Dwi Rahmadiane; Nurul Mahmudah; Yusri Anis Faidah; Tsalis Kholifatin Adil Mutamimmah; Nizar Fahrezi Majid (Universitas Islam Malang, 2023)
The role of teenagers is expected to accelerate the effectiveness and efficiency of BUMDes management because the phenomenon that occurs is that several BUMDes in Brebes Regency are not running optimally, one of which is because BUMDes managers are mostly from older people whose roles are more strategic and already have other activities so they lack management skills. and technically they need help from teenagers, one of which is in projecting their business units. The aims of this activity was to increase new skill and insight regarding optimizing BUMDes management using forecasting methods, increase the body of knowledge, and can become a reference for other parties who wish to carry out activities with a similar theme. The forms of activity include training on optimizing BUMDes management by delivering lectures, discussions and CBL or students can solve a case using the method that has been presented using the Forecasting Method. The implementation stages used are preparation, socialization, counseling, training and also evaluation. This article show results of succeeded increased the participants' skills and knowledge regarding managing Bumdes using the forecasting method with very good post-test results compared to the previous pre-test.